DEVELOPMENT OF VISUAL QUALITY EVALUATIVE ASSESSMENT METHOD IN CAMPUS LANDSCAPE - Firmansyah Firmansyah; Iwan Sudradjat; Widjaja Martokusumo; Budi Faisal (TATALOKA, 2017)
The design of campus landscape is expected to reflect the institution values, provide the character and the spirit of place to campus environment. It is highly influenced by visual experience and impression of campus environment. There are two methods in landscape visual quality assessment: descriptive assessment method and evaluative assessment method. Both assessment methods cannot be done simultaneously, but as a sequence phase. Descriptive assessment method should be done first to obtain a reference for evaluative assessment method. Landscape visual quality evaluative assessment method is used to measure the level of public assessment about visual quality and visual response. Information Processing Theory is used to develop the visual quality evaluative assessment method and to obtain unified integration between descriptive assessment and evaluative assessment. The development of evaluative assessment method includes the process of comparing, averaging, or determine the ranking of each environmental hue or landscape areas in campus, based on the public or college user community preferences.